A Small Nation in the Turmoil of the Second World War Money, Finance and Occupation (Belgium, its Enemies, its friends, 1939-1945) - Van der Wee, Herman (Leuven University Press, 2009)
This monograph presents an in-depth analysis of Belgium's monetary and financial history during the Second World War. Exploring Belgium's financial and business links with Germany, France, The Netherlands, Great Britain, the United States, and the Grand Duchy of Luxembourg, the study focuses on the roles played by the Central Bank and private bankers in Brussels, by the Belgian government in exile in London, and by the Belgian minister plenipotentiary in New York. Among the subjects arising are: German attempts to plunder Belgium and Belgian resistance strategies; the peripeteia of the Belgian gold reserve; the role of the Belgian Congo; Belgium's participation in the discussions leading up to the Bretton Woods conference; and the negotiations for creating a Customs Union, blueprint for the 1958 Treaty of Rome. The final part of the book analyzes the famous monetary reform devised by Belgian Minister of Finance Camille Gutt at the liberation of the country in September 1944.